Compact Photonic Transmitter Based on Annular Ring Antenna for THz Applications - Ibtissame Moumane; Jamal Zbitou; Ahmed Errkik; Larbi El Abdellaoui; Abdelali Tajmouati; Mohamed Latrach (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2018)
This paper presents the design of Continuous Wave Terahetz photonic transmitters based on photodector which convert the light signal to electrical signal, THz antenna, low-pass filter (LPF) and DC Probe. In the design of the CW THz photonic transmitter System, we begin with the matching input impedance and validation of THz antenna using an EM solver Momentum integrated in ADS “Advanced Design System”. Then we pass to the optimization of a low-pass filter which had the role of inductance, blocking the RF signal providing from the antenna to reach the DC probe. Finally, we associate the previous structures with a DC probe and simulate the whole circuit until validating the CW THz photonic transmitter circuit. The three structures are based on multi-layers GaAs substrate, which is the most widely used for THz circuit design. The dimensions of the whole circuit are 819.071 × 164.10 ????????2.